Foreign policy analysis beyond North America - Brummer, Klaus; Hudson, Valerie M., 1958- (Lynne Rienner Publishers, Inc., 2015)
North American scholars typically do not hesitate to make pronouncements about foreign policy processes and outcomes in other countries. And despite ample evidence to the contrary, the perception that foreign policy analysis is still largely a North American scholarly enterprise persists. Foreign Policy Analysis Beyond North America challenges this perception, providing a rich overview of work by scholars in Africa, Asia, Europe, Latin America, and the Middle East and also highlighting theoretical and empirical insights that may catalyze new waves of progress in the field.--Provided by publisher.